Pengembangan Media Pembelajaran Matematika Materi Keliling dan Luas Bangun Datar Menggunakan Animasi Powtoon di Kelas IV SD Universitas Muhammadiyah - Aprilia Fani Sabilla; Sony Irianto; Badarudin Badarudin (Peneliti.net, 2020)
Learning media that fit the needs of the 21st century today are digital-based learning media, one of them is media in the form of animated videos. Learning animation media for mathematics in grade IV at SD UMP is a media that does not yet exist and needs to be developed. This research method is research and development using the 4D model. The results of the validity of the feasibility of instructional media in this study in terms of media presentation and programming results obtained 46,6 included in the excellent category. Based on the results of research that has been done to get very good student enthusiasm, this is evidenced by the results of student questionnaire data when using animation media. Student questionnaire data obtained by 30 students (83%) included in the excellent category and the results of the teacher's response to the animation learning media in terms of appearance and material obtained 4.53 results included in the very good category. Completeness of student learning outcomes after using powtoon animation-based mathematics learning media, based on data analysis of student learning outcomes obtained results of 21 students reaching KKM, and 7 students not reaching KKM out of 28 students who took the post-test. This means that the completeness of learning outcomes of class IV SD UMP students in classical is 75% included in the high category.